Optimal Classes of Chemotherapeutic Agents Sensitized by Specific Small-Molecule Inhibitors of Akt In Vitro and In Vivo - Shi, Yan (Neoplasia Press, Inc., 2005)
Akt is a serine/threonine kinase that transduces survival signals from survival/growth factors. Deregulation and signal imbalance in cancer cells make them prone to apoptosis. Upregulation or activation of Akt to aid the survival of cancer cells is a common theme in human malignancies. We have developed small-molecule Akt inhibitors that are potent and specific. These Akt inhibitors can inhibit Akt activity and block phosphorylation by Akt on multiple downstream targets in cells. Synergy in apoptosis induction was observed when Akt inhibitors were combined with doxorubicin or camptothecin. Akt inhibitor–induced enhancement of topoisomerase inhibitor cytotoxicity was also evident in long-term cell survival assay. Synergy with paclitaxel in apoptosis induction was evident in cells pretreated with paclitaxel, and enhancement of tumor delay by paclitaxel was demonstrated through cotreatment with Akt inhibitor Compound A (A-443654). Combination with other classes of chemotherapeutic agents did not yield any enhancement of cytotoxicity. These findings provide important guidance in selecting appropriate classes of chemotherapeutic agents for combination with Akt inhibitors in cancer treatment.